2010
DOI: 10.1111/j.1651-2227.2010.01730.x
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in Norwegian children: prevalence and socio‐demographic risk factors

Abstract: The prevalence of OWOB and OB in Norwegian primary school children is of concern. Socio-demographic factors have pronounced effects on the current prevalence of overweight and obesity in a cohort of Norwegian children. This knowledge could help to work out strategies to reduce the burden of overweight and obesity in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
103
9
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(149 citation statements)
references
References 26 publications
27
103
9
7
Order By: Relevance
“…Similarly, other studies conducted in the same age group showed that males are more likely to be overweight than females (13,14,25,26). However, there are also studies claiming that obesity risk is higher in girls than boys (25,27,28). This study found no significant relationship between gender and obesity.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, other studies conducted in the same age group showed that males are more likely to be overweight than females (13,14,25,26). However, there are also studies claiming that obesity risk is higher in girls than boys (25,27,28). This study found no significant relationship between gender and obesity.…”
Section: Discussioncontrasting
confidence: 54%
“…However, this association was measured by two different socio-economic variables. Among the older group, the education level of the mother was used as a proxy to measure socio-economic status, as shown by Nagel et al (28) and Júlíusson et al (7) . These authors found that the education level of the mother as a socio-economic variable was an important factor for overweight in children.…”
Section: Discussionmentioning
confidence: 99%
“…They are also more likely to have other longerterm problems, such as cardiovascular and other related diseases, resulting in greater morbidity and mortality in adulthood (6) . Studies have shown that sociodemographic factors such as age, gender, number of siblings and the education level of parents are significantly associated with overweight (7) . Regarding this association, data in the Brazilian literature are in disagreement.…”
mentioning
confidence: 99%
“…This is in agreement with previous studies that have shown a higher obesity rate in single parent families (30)(31)(32). It has been hypothesized that this association is attributable to a lower income, with choice of cheaper and less healthy food and less time available to support physical activity as a consequence (33).…”
Section: Discussionmentioning
confidence: 99%